Dieu ou les hommes ? Vivre l’obéissance dans les couvents anglais en exil (1598-1688) - Laurence LUX-STERRITT (E-REA)
In the first half of the seventeenth century, more than sixty years after the dissolution of the monasteries in England, new English convents were founded on the Continent. After living their faith under penalty, those who chose exile in order to take the veil took part in the movement of renewal and Catholic reform inaugurated by the Council of Trent. Nuns were bound by enclosure and must obey their male superiors. Their confessors guided their spiritual lives with precise methods, according to the Spiritual Exercises of Ignatius Loyola, founder of the Society of Jesus. However, if the majority of English convents willingly conformed with this approach of monastic life, some appeared to disagree with that particular principle. The Benedictines of Cambrai and Paris, in particular, opted for a different path towards sacred union. They chose to be inspired by the mystics and by the examples of the great medieval saints which their spiritual director, Augustine Baker, incited them to discover on their own to meet God without the mediation of confessors or of their exercises. This mystically-inspired spirituality met with the censorship of the nuns’ superiors, who condemned it as rebellious, anti-authoritarian, and as a sure way to lead the religious to damnation.